Streaming from stage to screen: its place in the cultural marketplace and the implication for UK arts policy. Issue 2 (4th March 2018) - King, Timothy
Abstract : Live streaming of stage performances by opera and theatre companies into cinemas, and increasingly into the home, continues to grow rapidly. What the cinema audience hears and sees differs qualitatively both from what is seen in the theatre and also from what is normally available in cinemas. The 'real-time liveness' offered by leading companies appears to be an important attraction, though may diminish as the novelty of streamed performances wears off. The cinema audience is both socio-demographically and in cultural experience more similar to the theatre audiences than to typical cinema audiences, giving rise to suggestions that streaming might cannibalise the live audiences of the transmitting theatres, but there is no evidence of this, nor, at least in the UK, to support speculation that streaming reduces audiences for regional arts companies. Streaming should therefore be welcomed as broadening the number of consumers who can benefit from arts subsidies.